Inventory of plants in the Mangrove Botanic Garden of Gunung Anyar and their potential as medicinal plants - Melisnawati H. Angio; Elga Renjana; Linda Wige N ingrum; Elok Rifqi Firdiana; Rony Irawanto (Jurnal Penelitian Kehutanan Wallacea, 2022)
Mangrove forest is located along the coastal area and regularly waterlogged because it is influenced by the tides, and has an important ecological function for life. Mangrove forest, especially in urban areas, is the most threatened and damaged ecosystem. Surabaya has a mangrove forest in the Mangrove Botanic Garden of Gunung Anyar (MBGGA) with an area of 32,761 m2 and has the potential for educational tourism. Scientific information concerning plant species in MBGGA is needed to support this potential. This study aimed to inventory the mangrove plants and their associated species in MBGGA and their potential as medicinal plants. The inventory was carried out by tracking method while information on medicinal potential was obtained through literature study. The results showed that MBGGA had 14 mangrove species and 11 mangrove-associated species. Around 18 species are included in the least concern category and one in the vulnerable category of the IUCN red list. All plant species in MBGGA also have potential as medicinal plants and almost all their parts, including leaves, fruit, bark, and roots, can be used for that purpose. This study showed that MBGGA was rich in mangrove species and their associated plants which were potential as medicine.